Development of A Comprehensive IoT-Based Monitoring Application for High-Risk Pregnancies Enhancing Maternal and Fetal Health Outcomes - Matharasi , P. Bavithra; Selvam , Prabu; Sharma, Himanshu; Sugumar, D.; Kumar, Midathada Vinay; Rosaline, S.; Mounika, Addanki; Kanth , Tati‎raju V. Rajani (International Journal of Basic and Applied Sciences, 2025)
This paper presents the design, development, and testing of MAVATI, a mobile health application focused on perinatal monitoring for ex-‎expectant mothers and healthcare professionals. The system includes real-time monitoring of biomedical parameters, alert generation (both ‎manual and automatic), and a personalized recommendation module. Developed as a minimum viable product (MVP) for both patient and ‎physician interfaces, the application was evaluated through usability testing and load testing to validate its performance and user-friendliness. ‎Usability tests demonstrated intuitive navigation and effective interaction with key functionalities, while load testing using Apache JMeter ‎confirmed the system’s scalability and reliability under concurrent access. The results indicate that MAVATI is a responsive and user-centered solution capable of supporting maternal healthcare monitoring. Further clinical validation is recommended to assess its real-world ‎effectiveness and potential for data-driven research‎.